Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Sambal Dadakan Bang Jali Di Kota Bekasi - Prayuda Putra Ariansyah; Widi Winarso; Kardinah Indrianna Meutia; Milda Handayani; Rini Wijayaningsih (Pusat Riset dan Inovasi Nasional, 2024)
Sambal Dadakan Bang Jali is a type of UKM culinary business located in Bekasi City. This business was founded in 2020 during the COVID-19 pandemic and at that time only the company implemented a take away strategy. This study aims to determine the effect of product quality and service quality on purchasing decisions for Sambal Dadakan Bang Jali in Bekasi City. This study uses a type of Quantitative research. The population of this study were customers / visitors of Sambal Dadakan Bang Jali in Bekasi City. The sample collection method used is Non-Probability Sampling. Purposive sampling is a sampling approach method with the hair formula and a sample of 80 respondents. Data collection by means of observation, interviews, and questionnaires, data analysis using multiple linear regression methods. The results stated that product quality has a significant effect on purchasing decisions, while service quality has a significant effect on purchasing decisions and then simultaneously product quality and service quality affect purchasing decisions.